Real-Time Environmental Parameters Monitoring System - Davor Ćorić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
The objective of the RTEPMS (Real-Time Environmental Parameters Monitoring System) project is to design and implement a general-purpose environmental parameter monitoring system. The main focus is on measuring water quality parameters is several use cases. To achieve this goal, monitoring will be based on widely available, relatively cheap Internet of Things (IoT) based hardware. One of the most important use cases, drinking water quality monitoring, is piloted in cooperation with Regional Waterworks for the Montenegrin Cost (RWMC). RWMC is the largest drinking water supply company in Montenegro. Using the 135 km of pipelines it delivers drinking water of the highest quality to the Montenegrin coast. Beside drinking water monitoring use case, other use cases will be implemented and executed, such as water quality monitoring for fish farming as well as the pool (swimming) water quality monitoring.
Keywords: Q59; 330; platform; data integration; smart system; processing; sensor